Review of research in the area of agriculture mobile robots - Hajjaj S.S.H.; Sahari K.S.M. (Springer Verlag, 2023)
Rise in demand for food worldwide has led the agriculture industry to shift towards Corporate Agriculture; major conglomerates operate huge lands with Precision Farming; maximizing outputs and utilization of resources while reduce waste and costs. This efficiency required the introduction of Automation and Robotics in Agriculture, which led to great technological challenges. This in turn sparked interest in research in the area of Agriculture Mobile Robots (AMRs). This paper reviews research in this area for the last 5 years; it highlights examples of robots already in action in fields around the world, identifies trends and important sub-topics, and finally outlines the direction of where research in Mobile Agriculture Robots is heading. © 2014 Springer Science+Business Media Singapore.